The country-mans new art of planting and graffing : directing the best way to make any ground good for a rich orchard, with the manner how to plant and graffe all sorts of trees, to set and sow curnels : as also the remedies and medicines concerning the same, with divers other new experiments / practised by Leonard Mascall. (1652)
Summary goes here